Influência da Kisspeptina na etapa de seleção espermática para a produção in vitro de embriões bovinos - Soares, Mayara Mafra (2018)
The aim of the present study was to evaluate the addition of Kisspeptin (Kp) in the in vitro process of spermatic selection, regarding the viability of bovine spermatozoa and embryo production rates. For this, 980 oocytes were obtained from slaughterhouse ovaries and 75 commercial bovine semen straws were used. The treatments were performed on the spermatozoa during the in vitro spermatic selection stage by the centrifugation method with 90% and 45% Percoll® discontinuous gradients according to each proposed treatment: Control (n = 182), Kp 10-5 M (n = 198 ), Kp 10-6 M (n = 200), Kp 10-7 M (n = 206) and 50 μM P-234 antagonist (n = 194), with the dilutions carried out on both gradients respected concentrations. The spermatozoa were analyzed before and after spermatic selection for motility and vigor, and were submitted to staining with fluorescent probes JC-1, IP and FITC-PSA, to evaluate the mitochondrial potential, plasma membrane integrity and acrosome integrity under confocal laser scanning microscope LSM 510 meta. After the treatments, spermatozoa were normally used in IVEP procedures. The production analyzes were performed on D2 and D7, based respectively on cleavage and blastocysts rates. The data were submitted to the normality and homogeneity test by guided analysis SAS, after were used the proc GLIMMIX procedure to evaluate the experimental model and later the Tukey-Kramer test for comparison of means. Differences are considered when P < 0.05. The results of motility, vigor and production rates were similar (P> 0.05) among all proposed treatments. The cleavage rate (n = 846) was higher than 82% and the percentage of blastocyst production (n = 331) higher than 29% in all treatments. The mitochondrial potential of Kp 10-6 and Kp 10-7 (92.6%) groups was higher (P <0.05) to the Control (89.8%) and P-234 (83.8%) groups, the latter being lower (P <0.05) than all other treatments. Plasma membrane integrity and acrosome integrity (PMI/AI) evaluations showed that treatments with Kp addition were similar, (P> 0.05) Kp 10-5 (88.9%/90.9%), Kp 10-6 (90.7%/91.8%) and Kp 10-7 (90.2%/91.4%) and the P-234 antagonist (90.5%/90.8%), respectively. The Kp 10-6 treatment presented a superior result (P <0.05) to the Control group (87.9%/89.1%). When correlating the variables analyzed by confocal microscopy, a significant and positive correlation was observed between high mitochondrial potential and plasma membrane integrity (r = 0.80; P <0.0001), acrosome integrity and high mitochondrial potential (r = 0 , 80, P <0.0001), plasma membrane integrity and acrosome integrity (r = 0.84, P <0.0001). Finally, it can be concluded that the balanced concentration of Kp provided greater viability to bovine spermatozoa related to mitochondrial potential, acrosome integrity and plasma membrane. The P-234 antagonist presented a detrimental effect on the mitochondrial potential.